Trust, impact, and fundraising for nonprofits : how meaningful ethics and strategic evaluation can multiply your revenue and expand your program - Phillips, Kenneth H. (New York, NY : Routledge, 2023)
"Distilling decades of leadership expertise into an effective framework, this is a practical guidebook for nonprofits around the globe, with practical recommendations for the urgently needed steps to make this a better world. Charities in the U.S. and NGOs globally need to overcome two glaring and persistent weaknesses in the eyes of potential donors: trustworthiness and effectiveness. After examining possible causes for these deficits, fundraising and organizational development guru Ken Phillips guides readers through the process that leads to greater trust and respect by donors, better results for beneficiaries, significantly increased funding, and better and bigger programs. Alongside helpful worksheets, he presents seven steps to make sure ethics are meaningful, eight disciplines to ensure programs achieve good results, and a communications approach to demonstrate responsibility and accountability, all interwoven with inspiring case studies from his own international experience and other organizations stories. Staff and volunteers at registered nonprofits around the world, as well as any individual or group raising funds more informally, will value this guide to empower organizations to win trust, raise more funds, and achieve greater program impact."--
OCLC-licensed vendor bibliographic record.
Keywords: Nonprofit organizations; Nonprofit organizations -- Moral and ethical aspects; Nonprofit organizations -- Finance